Short Communication: Diversity of culturable epiphytic bacteria isolated from seagrass (Halodule uninervis) in Thailand and their preliminary antibacterial activity - PARIMA BOONTANOM; Aiya Chantarasiri (Society for Indonesian Biodiversity, 2020)
Abstract. Boontanom P, Chantarasiri A. 2020. Short Communication: Diversity of culturable epiphytic bacteria isolated from seagrass (Halodule uninervis) in Thailand and their preliminary antibacterial activity. Biodiversitas 21: 2907-2913. Epiphytic bacteria are symbiotic bacteria that live on the surface of seagrasses. This study presents the diversity of culturable epiphytic bacteria associated with the Kuicheai seagrass (H. uninervis) collected from Rayong Province in Eastern Thailand. Nine epiphytic isolates were identified into four phylogenetical genera based on their 16S rRNA nucleotide sequence analyses. They are considered firmicutes in the genera of Planomicrobium, Paenibacillus and Bacillus, and proteobacteria in the genus of Oceanimonas. Three species of epiphytic bacteria preliminarily exhibited antibacterial activity against the human pathogenic Staphylococcus aureus using the perpendicular streak method. The knowledge obtained from this study increases understanding the diversity of seagrass-associated bacteria in Thailand and suggests the utilization of these bacteria for further pharmaceutical applications.